The Influence of Product Quality on Customer Satisfaction and Loyalty at Laritta Bakery Shop Dharmahusada Surabaya - Utami, Wahyu; Herawati, Andry; Sarwani, Sarwani; Liling Listyawati (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of product quality on customer satisfaction and loyalty at Laritta Bakery Shop Dharmahusada Surabaya. The study originates from a research gap that has not specifically explored the dimensions of product quality in shaping customer satisfaction and loyalty in the bakery industry. This research employs a quantitative method with a causal associative approach. The sample consists of 96 respondents selected using Simple Random Sampling. Data were analyzed using descriptive analysis and path analysis. The results show that product quality has a significant influence on customer satisfaction (β = 0.398; t-value = 5.538; p = 0.000) and customer loyalty (β = 0.661; t-value = 10.298; p = 0.000). Customer satisfaction also significantly affects customer loyalty (β = 0.317; t-value = 3.181; p = 0.001), although its impact is smaller compared to product quality. These findings highlight the importance of improving product quality, particularly in terms of reliability, aesthetics, and durability, to enhance customer satisfaction and loyalty. This study provides strategic contributions for Laritta Bakery in increasing competitiveness and retaining customers.